2016
DOI: 10.1103/physreva.94.043642
|View full text |Cite
|
Sign up to set email alerts
|

Long-range ordering of topological excitations in a two-dimensional superfluid far from equilibrium

Abstract: We study the relaxation of a two-dimensional (2D) ultracold Bose gas from a nonequilibrium initial state containing vortex excitations in experimentally realizable square and rectangular traps. We show that the subsystem of vortex gas excitations results in the spontaneous emergence of a coherent superfluid flow with a nonzero coarse-grained vorticity field. The stream function of this emergent quasiclassical 2D flow is governed by a Poisson-Boltzmann equation. This equation reveals that maximum entropy states… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…Our results indicate that, during the coarsening process, the scaling exponent β switches from the anomalous to the Gaussian value, when the clustering of like-sign defects disappears, see figures 7 and 9. Hence, it is imaginable that in a driven situation, with a vortex ensemble containing a constant number of defects on average and representing a state close to the clustering transition of [88,89], the respective critical dynamics is related to the anomalous fixed point we report here.…”
Section: Three-body-collision Induced Vortex Lossmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results indicate that, during the coarsening process, the scaling exponent β switches from the anomalous to the Gaussian value, when the clustering of like-sign defects disappears, see figures 7 and 9. Hence, it is imaginable that in a driven situation, with a vortex ensemble containing a constant number of defects on average and representing a state close to the clustering transition of [88,89], the respective critical dynamics is related to the anomalous fixed point we report here.…”
Section: Three-body-collision Induced Vortex Lossmentioning
confidence: 91%
“…For charge-neutral atoms in a closed trap without external fields, a potentially related clustering transition has been reported [88,89]. Onsager's point-vortex model [79] implies a maximum entropy state in which an equal number of elementary vortices and anti-vortices are randomly distributed in the system.…”
Section: Three-body-collision Induced Vortex Lossmentioning
confidence: 99%
“…The successes of the recent experimental developments have also spawned novel theoretical investigations [13,[34][35][36][37][38][39][40][41][42][43][44][45]. In addition to visual inspection, the presence of Onsager vortices has been associated with indicators such as the vortex dipole moment [13,34], vortex clustering measures [7,8,36,37,40], or a peak in the power spectral density of incompressible kinetic energy [8,13,38,46].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, many recent theoretical works involving superfluid Bose-Einstein condensates (BECs) have suggested that largescale, same-sign Onsager vortex clusters play an important role in 2D quantum turbulence [8][9][10][11][12][13][14][15][16][17]. In superfluids, much of the focus to date has been on decaying-rather than driventurbulence [9,[11][12][13][14][17][18][19][20][21][22][23][24], since this scenario removes the complications of stirring. A variety of concepts have been applied to the problem, including holographic duality [25,26] and nonthermal fixed points [27][28][29].Experimentally, BECs provide unprecedented opportunities to investigate 2D superfluid turbulence due to the high degree of controllability available in these systems.…”
mentioning
confidence: 99%